2019
DOI: 10.1109/jstsp.2019.2934931
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Enhanced Massive MIMO With Array Signal Processing Techniques

Abstract: In the past ten years, there have been tremendous research progresses on massive MIMO systems, most of which stand from the communications viewpoint. A new trend of investigating massive MIMO, especially for the sparse scenario like millimeter wave (mmWave) transmission, is to re-build the transceiver design from array signal processing viewpoint that could deeply exploit the half-wavelength array and provide enhanced performances in many aspects. For example, the high dimensional channel could be decomposed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 157 publications
(264 reference statements)
1
71
0
Order By: Relevance
“…, √ P K is a diagonal power allocation matrix that satisfies the power constraint, i.e., the total transmit power K j=1 P j = P . For ease of exposition, the power is equally allocated amongst users, 5 i.e., P = [14], [24], [27]. Furthermore, it is observed that some of the r k nonzero eigenvalues of Σ k are extremely small, and as such could be ignored, resulting in an effective rank of r eff, k r k N BS .…”
Section: B Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“…, √ P K is a diagonal power allocation matrix that satisfies the power constraint, i.e., the total transmit power K j=1 P j = P . For ease of exposition, the power is equally allocated amongst users, 5 i.e., P = [14], [24], [27]. Furthermore, it is observed that some of the r k nonzero eigenvalues of Σ k are extremely small, and as such could be ignored, resulting in an effective rank of r eff, k r k N BS .…”
Section: B Notationsmentioning
confidence: 99%
“…Traditionally, in FDD systems, the acquisition of channel statistics information at the transmitter is acquired through long-term DL training sequences and low-rate UL feedback. However, channel statistics reciprocity is being leveraged for FDD systems more recently [24], [32]- [34]. This key observation eliminates the need for channel statistics estimation and feedback in FDD systems, and results in significant training and feedback overhead reduction.…”
Section: Statistical Csitmentioning
confidence: 99%
“…where α k , d, and λ denote the propagation gain of the k th downlink path and the antenna spacing at the BS and carrier wavelength, respectively. d = 1 2 λ is widely adopted here [32]. δ T,k ∈ [0, 2π] is the AoD of the k th path.…”
Section: System Modelmentioning
confidence: 99%
“…In [ 27 ], a virtual channel with common sparsity because users are sharing the same local scatters, is explained in which the information of unitary dictionary matrix is available at a base station (BS). A comprehensive study on signal processing techniques used for mmWave MIMO communications is briefly explained in [ 28 ].…”
Section: Introductionmentioning
confidence: 99%